Evaluation of fungal mixed cultures for production of citric acid using empty fruit bunches by solid state bioconversion - Alam, Md.; Bari, Md. Niamul; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah (2008)
The filamentous fungal strains of Aspergillus niger O-103A, O-109A and O-114A isolated from orange were selected for the evaluation of compatible/incompatible for the production of citric acid by mixed culture. Four combinations of O-103A and O-109A; O-103A and O-114A; O-109A and O-114A; O-103A, O-109A and O-114A were used to examine their potentiality in terms of compatible/incompatible mixed culture through citric acid production. The experiment was carried out to observe the productivity of citric acid in 250 ml Erlenmeyer flasks. The result obtained through this study showed that every culture of fungal combinations was inhibited to produce of citric acid by presence of other strain. The maximum production of citric acid obtained from the single culture of O-114A was 181.251.5 g/kg of dry EFB which was 2 times higher than the maximum production by the mixed culture of O-109A and O-114A.